Ulil Albab: An Ancient Methodology for Building Corporate Spiritual Responsibility (CSpR) - Rismawati, Rismawati; Retnowati, Wulan; Supriadi, Supriadi (Journal of Applied Business, Taxation and Economics Research, 2024)
Corporate Social Responsibility (CSR) aims to balance economic, social, and environmental impacts, but often lacks spiritual and ethical depth. This research introduces Corporate Spiritual Responsibility (CSpR) using the Ulil Albab methodology, rooted in Islamic tradition. The Ulil Albab method integrates intellectual and spiritual faculties through Zikir (remembrance), Do’a (prayer), Tafakur (reflection), and Tahanuts (seclusion), known collectively as ZDTT. By grounding CSR in spiritual awareness, this approach fosters more authentic and impactful social responsibility. The methodology combines sensory perception, rational thought, heart intuition, and divine revelation, offering a holistic approach to knowledge. Implementing CSpR aligns corporate actions with spiritual principles, ensuring ethical integrity and sustainability. The study explores how CSpR can transform CSR practices, its practical implications, and its role in creating a more ethical corporate culture. CSpR enhances businesses' moral fabric, helping them navigate ethical dilemmas and build stakeholder trust.